2018
DOI: 10.3389/fmars.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Fishermen Follow Fine-Scale Physical Ocean Features for Finance

Abstract: The seascapes on which many millions of people make their living and secure food have complex and dynamic spatial features-the figurative hills and valleys-that influence where and how people work at sea. Here, we quantify the physical mosaic of the surface ocean by identifying Lagrangian Coherent Structures for a whole seascape-the U.S. California Current Large Marine Ecosystem-and assess their impact on the spatial distribution of fishing. We observe that there is a mixed response: some fisheries track these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 80 publications
(97 reference statements)
0
40
0
Order By: Relevance
“…For example, tuna fishermen may be three times more profitable if fishing on strong oceanographic fronts (i.e. Lagrangian coherent structures; Watson et al, 2018). This implies that the effects of a physical feature of the water column can trickle through the local food web, ultimately affecting fisheries profitability at the spatial and temporal scale of the physical feature.…”
Section: Priority Iv: Consider Ecosystem Spatio-temporal Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tuna fishermen may be three times more profitable if fishing on strong oceanographic fronts (i.e. Lagrangian coherent structures; Watson et al, 2018). This implies that the effects of a physical feature of the water column can trickle through the local food web, ultimately affecting fisheries profitability at the spatial and temporal scale of the physical feature.…”
Section: Priority Iv: Consider Ecosystem Spatio-temporal Variabilitymentioning
confidence: 99%
“…Human activities can interact directly and indirectly with a variety of natural drivers, such as shear stress, storms or currents, at different spatio-temporal scales (van Denderen et al, 2015;Watson et al, 2018). These interactions may trigger biodiversity responses that consequently appear at different levels of organization, influencing both faunal composition and functions that ultimately impact ecosystem functions and services.…”
Section: Priority Iv: Consider Ecosystem Spatio-temporal Variabilitymentioning
confidence: 99%
“…The temporal scale associated with these horizontal and vertical fine scales is days to weeks, the same as in many important ecological processes including phytoplankton demography and competition, and the duration of foraging trips for many marine predators. This temporal resonance is one of the reasons behind the fine-scale variability that appears in marine ecosystems and their services, including biogeochemical cycles (Lévy et al, 2012;Olita et al, 2013;McGillicuddy, 2014;d'Ovidio et al, 2015;Mahadevan, 2016;Lehahn et al, 2018), biodiversity (d'Ovidio et al, 2010;Lévy et al, 2015), fish distribution (Godø et al, 2012;Watson et al, 2018), and even foraging strategies of megafauna (Tew Kai et al, 2009;Della Penna et al, 2017).…”
Section: Importance Of Fine Scalesmentioning
confidence: 99%
“…Biophysical couplings at fine scales present large uncertainties, introducing a notorious main source of error in representing ocean dynamics on a variety of interdisciplinary issues, ranging from the biological carbon pump and its associated export (Lévy et al, 2012;Siegel et al, 2016) to plankton diversity and spatial planning of commercial fisheries (Scales et al, 2018;Watson et al, 2018) and marine protected areas (Della Penna et al, 2017). The observations during the SWOT fastsampling phase present a novel opportunity for studying the ecology of microbial populations, in particular when paired with high throughput techniques.…”
Section: Science Opportunities For Physical and Biophysical Processesmentioning
confidence: 99%
“…However, while the influence of Lagrangian fronts has been observed on both extremes of the trophic chain, much less is known about mid-trophic levels. Prants et al (see in particular Prants et al, 2014) demonstrated a correlation between Pacific saury catches and Lyapunov exponents, and Watson et al (2018) found that several fishery vessels track LCSs when targeting fishery spots. However, these results leave some concerns about possible biases because commercial fisheries provides only punctual observations, and because they are even known to use satellite images.…”
Section: Introductionmentioning
confidence: 99%